Efficacy of Artesunate versus a Combination of Artesunate and Quinine Di-Hydrochloride Given Intravenously for the Treatment of Malaria; A Comparative Study: Efficacy of Artesunate and Quinine Di-Hydrochloride for the Treatment of Malaria - Akbar, Asma; Jabeen, Irum; Kanwal, Kiran; Ilyas, Sonia; Ahmad, Shakeel (Pakistan Journal of Health Sciences, 2024)
In developing countries, malaria is still one of the leading causes of morbidity and mortality. Objectives: To evaluate the efficacy of intravenous artesunate alone versus intravenous combination of artesunate and quinine. Methods: This randomized control trial was conducted in the Pediatric Medicine Unit-2, Allama Iqbal Teaching Hospital, Dera Ghazi Khan, Pakistan. The inclusion criteria were children of either gender, aged 2-14 years and admitted to the emergency department with the diagnosis of severe malaria. Children were randomly allocated to two treatment groups of equal size. The intravenous artesunate group received artesunate administered intravenously for a maximum of 7 days. The intravenous combination of artesunate and quinine group received artesunate intravenously combined with quinine di-hydrochloride intravenously for a maximum of 7 days. they were employing the lottery method. The outcome was measured as the number of hours elapsed for an individual to become fever-free (temperature below 36.8°C). Results: In a total of 104 children with severe malaria. the mean duration required to become fever-free was 28.3 ± 5.4 hours in intravenous artesunate alone versus 26.5 ± 6.4 hours in intravenous combination of artesunate and quinine groups (p=0.1242). The most frequent treatment-related side effects were nausea, loss of appetite, hypoglycemia, diarrhea, and rash, noted in 21 (20.2%), 13 (12.5%), 11 (10.6%), 5 (4.8%), and 2 (1.9%) patients, respectively. Conclusions: It was concluded that intravenous artesunate and quinine together did not provide any additional benefit or synergistic effect over intravenous artesunate alone in treating severe malaria in children.